Pengendalian Kualitas Produk Oven Tangkring Menggunakan Metode Seven Quality Tools dan Kaizen - Ryan Ardiansyah; Atikha Sidhi Cahyana (Indonesian Journal Publisher, 2026)
UKM ANDA, a manufacturing company engaged in the field of kitchen equipment, especially ovens. Experiencing a problem, namely high product defects reaching 3-5% per month. The purpose of this study is to identify the types of defects in the product, find the causes of product defects, and provide suggestions for improvement to reduce product defects. Using the seven quality tools and kaizen methods, it shows the types of defects that occur, namely dent defects of 89 products (40%), dimensional defects of 77 products (34%), and stand defects of 59 products (26%). Human factors (carelessness), methods (unclear work instructions), machines (blunt cutting tools), materials (poor raw materials), and the environment (messy work area) contribute to product defects. Proposed improvements include providing briefings, creating appropriate work guides for the production process, checking raw materials, periodic maintenance, and arranging work tools.